The Effect of Price and Product Quality on Purchase Decision of Aqua Drinking Water Product in Malang City - Zulfikar, Muhammad; Wijaya, Rahmad; Andharani, Sri Nastiti (Universitas Muhammadiyah Malang, 2023)
This study aims to determine the effect of price and product quality on the purchasing decision of Aqua drinking water products in Malang City. Using a quantitative approach, this research was conducted on 150 Aqua consumers and analyzed using multiple regression analysis. The results of this study conclude that price has a significant positive effect on purchasing decisions. Product quality has a significant positive effect on purchasing decisions. Product quality is more dominant than price in purchasing decisions.